Vaccination and infectious diseases: a never ending story (Italian Journal of Public Health, 2012)
The relationship between vaccine and infectious diseases can be easily considered a never ending story. In the 3rd issue of 2009 of this journal, thematic papers were related to vaccination policies and practice, with a particular focus on vaccine and vaccination evalu- ation and assessment....